Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð±Ñ‹ÑÑ‚Ñ€Ð¾Ð³Ð¾ Ð´Ð²ÑƒÑ…ÑÑ‚ÑƒÐ¿ÐµÐ½Ñ‡Ð°Ñ‚Ð¾Ð³Ð¾ Ð·Ð°Ð¼Ð¾Ñ€Ð°Ð¶Ð¸Ð²Ð°Ð½Ð¸Ñ Ð½Ð° ÑÐ¾Ñ…Ñ€Ð°Ð½Ð½Ð¾ÑÑ‚ÑŒ ÐºÐ»ÐµÑ‚Ð¾Ðº ÐºÐ¾ÑÑ‚Ð½Ð¾Ð³Ð¾ Ð¼Ð¾Ð·Ð³Ð° - Ostankov, M. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
Supercooling of murine bone marrow intracellular solution under cell suspension cooling with a constant rate and at a rapid twostepfreezing has been theoretically calculated. The optimal conditions for these cells cryopreservation under dimethyl sulfoxide protection have been determined, basing on the calculations and experiments performed.